Peningkatan Kualitas Pembelajaran RA Plus Al-Islam Simpangsari Garut melalui Optimalisasi Sarana Ekoedukasi Berbasis Pertanian - Asyiah, Iis Nur; Assiddiqi, Hasbi; Mudakir, Imam; Ellena FL Lilipaly (Universitas KH. Mukhtar Syafaat (UIMSYA), 2025)
The kindergarten can utilize its schoolyard as a supportive and ideal learning place in teaching and learning activities, especially regarding the environment. So far, RA Plus Al-Islam has not managed the schoolyard thoughtfully; they have only arranged it to fulfill the game tools. Considering the geographical conditions and the main livelihoods of the community around the school, RA Plus Al-Islam can use the schoolyard as an agricultural-based eco-education facility. The purpose of Service activity is to optimize the RA Plus Al-Islam schoolyard so that it is safe and comfortable to play and, at the same time, can function as an agriculture-based eco-education facility. The method of implementing activities is by lecture, discussion, practice, and mentoring, with the activity's target being RA teachers. The post-test results showed increased teacher knowledge about agriculture-based ecoeducation, with an average score of 90. Using the schoolyard as a means of agriculture-based eco-education increased the interest and enthusiasm of RA students in learning to care for plants.